Pengaruh Pertumbuhan Laba Dan Kepemilikan Manajerial Terhadap Nilai Perusahaan Pada Sektor Pertambangan - Resti; Resti, Resti; Jamal, Sri Wahyuni; Rahmah , Asmadhini Handayani (Manajemen Keuangan Syariah, 2025)
The mining sector in Indonesia plays a significant role in driving national financial growth. The abundance of natural resources makes Indonesia a leading producer natural resource outputs like coal, precious metals, and industrial minerals. This paper aims to examine how earnings expansion and executive shareholding affect firm firm valuation within IDX-listed mining companies between 2019 and 2023  timeframe. The method employed to gather data in this study is archival documentation obtaining data directly from each company's official public reports. The participants selected for this study include of 15 mining sector companies that meet the predetermined criteria. The research applies a statistical framework using multivariate regression of data examination. The findings indicate that earnings expansion meaningfully impacts firm value, indicating that the higher the profit growth, the greater the potential increase in firm value. On the other hand, managerial ownership fails to significantly influence company valuation, possibly because of the minimal portion of shares owned by management, which is not yet sufficient to provide a strong incentive to harmonize managerial objectives with investor priorities.